2013
DOI: 10.1103/physrevd.87.126003
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting dome from holography

Abstract: We find a regime in which a strongly coupled striped superconductor features a superconducting dome. This regime is signified by i) a modulating chemical potential that averages to zero, and ii) a superconducting order parameter that has a scaling dimension 3/2 < ∆ ≤ 3. We also find that in this regime, the order parameter exhibits a mild dependence on the modulation wavelength of the stripes.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
(30 reference statements)
0
7
0
Order By: Relevance
“…These can be first or second order phase transition as a function of the detailed form of the holographic theory. 24 The first attempt towards finding a superconducting dome from holography has been done in the Abelian-Higgs model [18] by introducing a modulating chemical potential [89]. It was shown that there is a critical modulation wave number above which the critical temperature will vanish or nearly vanish.…”
Section: Jhep01(2016)147mentioning
confidence: 99%
“…These can be first or second order phase transition as a function of the detailed form of the holographic theory. 24 The first attempt towards finding a superconducting dome from holography has been done in the Abelian-Higgs model [18] by introducing a modulating chemical potential [89]. It was shown that there is a critical modulation wave number above which the critical temperature will vanish or nearly vanish.…”
Section: Jhep01(2016)147mentioning
confidence: 99%
“…Introducing a spatially modulated source, such as a periodic chemical potential, can be interpreted as modeling an underlying lattice [8][9][10][11][12][13][14][15][16][17] or disorder [18,19], while a single localized source represents a defect [20][21][22]. Linearly varying scalar fields cause the weakest breaking, yielding a homogeneous stress tensor and allowing a more tractable analysis [23][24][25][26][27][28][29][30][31].…”
mentioning
confidence: 99%
“…tories, R, can de facto be disregarded compared to the P exchange). Setting s 1 ≈ s 2 , M ≈ 1 GeV, and √ s = 7 TeV and using the relation s 1 s 2 ≈ M 2 s (which holds for processes in the central region [192][193][194]), we obtain √ s 1 ≈ √ s 2 ≈ 84 GeV. Thus, the dominance of the PP exchange in LHC experiments is a very good approximation.…”
Section: Reactions Violating Isotopic Invariance In the Central Regionmentioning
confidence: 79%
“…Only resonances with positive C-parity and the isotopic spin I = 0 can be produced in a two-pomeron collision. The cross sections of processes driven by that mechanism do not decrease as a power of energy [24,173,[192][193][194]. Therefore, the observation of resonances in X 0 states with I = 1 is a signal that they are produced or decay with isotopic invariance violation.…”
Section: Reactions Violating Isotopic Invariance In the Central Regionmentioning
confidence: 97%
See 1 more Smart Citation